Efektivitas Promosi Kesehatan Permainan Ular Tangga Modifikasi terhadap Tingkat Pengetahuan tentang Protokol Kesehatan COVID-19 - Enisah Maksum; Nurharlina Nurharlina; Dyan K. Nugrahaeni; Iin Inayah; Mamat Lukman (Journal of Telenursing (JOTING), 2022)
This study aims to test the effectiveness of the modified snake and ladder game on the level of knowledge about COVID-19 health protocols in grade 1 elementary school (SD) students at SDN Karang Pawulang, Bandung City. The method used is a true experiment pre-test & post-test group control design. The results showed a difference between the pre-test and post-test scores obtained was 0.025. In conclusion, the modified snake and ladder game is effective in increasing the knowledge of grade 1 elementary school students about the COVID-19 health protocol. Keywords: COVID-19, Health Promotion, Health Protocol, Knowledge Level, Snakes and Ladders